Mechanisms by Which Traditional Chinese Medicines Influence the Intestinal Flora and Intestinal Barrier - Che, Qingya; Luo, Tingting; Shi, Junhua; He, Yihuai; Xu, De-Lin (Frontiers in Cellular and Infection Microbiology, 2022)
The effect of a drug on the intestinal flora and the intestinal barrier is an important evaluation index for drug safety and efficacy. Chemical synthetic drugs are widely used due to their advantages of fast efficacy and low doses, but they are prone to cause drug resistance and inhibit proton pumps, which may harm intestinal health. Traditional Chinese medicine (TCM) has been applied clinically for thousands of years, and how TCMs regulate intestinal health to achieve their effects of disease treatment has become a hot research topic that needs to be resolved. This paper reviews the recent research on the effects of TCMs on intestinal microorganisms and the intestinal mucosal barrier after entering the intestine, discusses the interaction mechanisms between TCMs and intestinal flora, and details the repair effect of TCMs on the intestinal mucosal barrier to provide a reference for the development, utilization, and modernization of TCM.